Prevalence of Stunting and Thinness Among Adolescent Girls Belonging to the Rajbanshi Population of West Bengal, India - Roy, Susmita; Barman, Sweeta; Mondal, Nitish; Sen, Jaydip (Journal of Nepal Paediatric Society, 2016)
Introduction: In India majority of the individuals remain undernourished. The primary causes of undernutrition are its large population, socio-economic differences and inadequate access to health facilities. Assessment of nutritional status among adolescents is very important as they are the future parents and constitute a potentially vulnerable segment of the population. The present school-based cross-sectional study evaluates the prevalence of stunting and thinness among adolescent girls from North Bengal. Materials and Methods: The present study was carried out among 500 Rajbanshi adolescent girls aged 9 to 18 years and residing in the districts of Darjeeling and Jalpaiguri in West Bengal, India. Anthropometric measurements of height and weight were recorded and body mass index (BMI) calculated. The prevalence of undernutrition was assessed using recommended anthropometric indices of stunting (low height-for-age) and thinness (low BMI-for-age), along with a comparison with the WHO reference population. Results: The overall prevalence of stunting and thinness was observed to be 39.60% and 26.00% respectively. The prevalence of age-specific stunting was higher and lower among girls aged 17 years (70.21%) and 10 years (24.00%), respectively. The age-specific prevalence of thinness was observed to be higher among those aged 10 years (66.00%) and lower among those aged 17 years (8.51%). Conclusion: There is a need for appropriate nutritional intervention programmes to address their nutritional needs. The results of the present study will also help policy makers to formulate various developmental and health care programmes. J Nepal Paediatr Soc 2016;36(2):147-155.